Enhanced static ground power unit based on flying capacitor based h‐bridge hybrid active‐neutral‐point‐clamped converter. Issue 12 (1st October 2016) - Abarzadeh, Mostafa; Kojabadi, Hossein M.; Deng, Fujin; Chen, Zhe
Abstract : Static power converters have various applications, such as static ground power units (GPUs) for airplanes. This study proposes a new configuration of a static GPU based on a novel nine‐level flying capacitor h‐bridge active‐neutral‐point‐clamped (FCHB_ANPC) converter. The main advantages of the proposed converter in comparison with conventional nine‐level ANPC converter are decreasing the number of switches and flying capacitors (FCs) in the proposed converter, doubling the output voltage level of a traditional ANPC converter and reduction of output L‐C filter sizes which results in significant improvement in GPU dynamic performances. This progress is achieved by utilising the proposed FCHB converter to an ANPC converter and using the suggested modulation method. This leads to diminish the size and cost and enhance the feasibility and reliability of the converter. Applying the proposed modulation method for FCs in the FCHB_ANPC converter guaranties self‐balancing and voltage level regulation of FCs without using closed‐loop control. Improved output voltage spectrum leads to inductance reduction of output L‐C filter which enhances static GPU performance. The simulation and experimental results demonstrate the validity and feasibility of the proposed converter and the modulation method under various operating conditions.